Epidemiology of zoonoses in slaughterhouse workers in western Kenya - Cook, Elizabeth A.J. (University of Edinburgh, 2014)
Slaughterhouses are places where animals are slaughtered for food. In developing countries a lack of appropriate facilities and limited resources mean the slaughter industry is poorly regulated. Poor hygiene practices in slaughterhouses can result in the transmission of diseases from animals to people called zoonoses. Slaughterhouse workers are generally considered at increased risk of being exposed to such diseases due to their close contact with animals and animal products. The aims of this study were: to assess the current conditions in slaughterhouses and the knowledge, attitudes and practices of workers in ruminant and pig slaughterhouses in Western Kenya; to determine the exposure of slaughterhouse workers to different zoonotic pathogens; to investigate the risk factors associated with exposure to these pathogens and to quantify the risk of zoonotic disease exposure for slaughterhouse workers compared to the general population. Slaughterhouses in Western Kenya were visited between May 2011 and October 2012. There were 738 workers recruited from 142 slaughterhouses. Overall, the slaughterhouses lacked facilities with 65% (95% CI 63–67%) of slaughterhouses having a roof, cement floor and solid sides, 60% (95% CI 57–62%) had a toilet and 20% (95% CI 18–22%) hand-washing facilities. Less than half of workers 32% (95% CI 29–34%) wore personal protective clothing. Antemortem inspection was practiced at 7% (95% CI 6–8%) of slaughterhouses and 18% (95% CI 16–19%) of workers reported slaughtering sick animals. Slaughterhouse workers were screened for five zoonotic diseases. The unadjusted seroprevalence of the zoonotic diseases were: brucellosis 0.1 (95% CI 0.007–0.8%); leptospirosis 13.4% (95% CI 11.1–16.1%); Q fever 4.5% (95% CI 3.2–6.2%); Rift Valley fever (RVF) 1.2% (95% CI 0.6–2.3%); taeniasis 1.8% (95% CI 1.0–3.0%); and cysticercosis 2.6% (95% CI 1.7–4.0%). Risk factors for leptospirosis and Q fever were examined by multivariable logistic regression. Risk factors associated with exposure to leptospirosis included: having wounds (OR 2.7; 95% CI 1.4–5.3); smoking at work (OR 1.8; 95% CI 1.1–3.0); eating at work (OR 2.1; 95% CI 1.2–3.6); and cleaning the intestines (OR 3.8; 95% CI 1.8– 8.2). Protective factors were: working at a slaughterhouse where antemortem inspection was performed (OR 0.6; 95% CI 0.4–0.9). The risk factors significantly associated with exposure to Q fever included: being intoxicated at work (OR 3.2; 95% CI 1.1–9.4). The odds ratio for leptospirosis seropositivity in slaughterhouse workers was determined to be 2.3 (95% CI 1.6–3.4) times that of the community. For Q fever the odds ratio for seropositivity in slaughterhouse workers was 1.9 (95% CI 1.0–3.8) times that of the community. This is the first report of a range of zoonotic pathogens in slaughterhouse workers in Kenya. This study indicated the potential risk factors for zoonotic disease exposure in slaughterhouses. The current working conditions in slaughterhouses in Western Kenya are far below the recommended standard. Improvements need to be made to facilities and practices in all slaughterhouses. Training is recommended to improve awareness for workers, managers and inspectors of the risks of meat contamination and methods to reduce it.